2013
DOI: 10.1158/1535-7163.mct-13-0025
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of the WEE1 Inhibitor MK-1775 as Single-Agent Anticancer Therapy

Abstract: Inhibition of the DNA damage checkpoint kinase WEE1 potentiates genotoxic chemotherapies by abrogating cell-cycle arrest and proper DNA repair. However, WEE1 is also essential for unperturbed cell division in the absence of extrinsic insult. Here, we investigate the anticancer potential of a WEE1 inhibitor, independent of chemotherapy, and explore a possible cellular context underlying sensitivity to WEE1 inhibition. We show that MK-1775, a potent and selective ATP-competitive inhibitor of WEE1, is cytotoxic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
145
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 43 publications
18
145
1
Order By: Relevance
“…The effects of MK-1775 on OCIP23 cells were much more dramatic than Wee1 knockdown, with the accumulation of cells in early S-phase showing H3S10 phosphorylation, associated with high levels of Cyclin A2 and Cyclin B1 that are normally highly expressed in late S-phase and G2. These effects have been previously observed, and attributed to premature entry of S-phase cells into mitosis, 19,20 which is consistent with the confocal microscopy features seen in Figure 2B. However, we did not observe them in the OCIP23 xenografts, even at the high dose of 80mg/kg (for comparison, the human maximum tolerated dose of 225mg twice daily 13 is roughly 6mg/kg), and it remains unclear if forced mitotic entry is a significant drug effect in humans.…”
Section: Mk-1775 (Now Azd1775supporting
confidence: 55%
See 2 more Smart Citations
“…The effects of MK-1775 on OCIP23 cells were much more dramatic than Wee1 knockdown, with the accumulation of cells in early S-phase showing H3S10 phosphorylation, associated with high levels of Cyclin A2 and Cyclin B1 that are normally highly expressed in late S-phase and G2. These effects have been previously observed, and attributed to premature entry of S-phase cells into mitosis, 19,20 which is consistent with the confocal microscopy features seen in Figure 2B. However, we did not observe them in the OCIP23 xenografts, even at the high dose of 80mg/kg (for comparison, the human maximum tolerated dose of 225mg twice daily 13 is roughly 6mg/kg), and it remains unclear if forced mitotic entry is a significant drug effect in humans.…”
Section: Mk-1775 (Now Azd1775supporting
confidence: 55%
“…18 Subsequently it was reported that treatment with the clinical Wee1 inhibitor MK-1775 (AZD-1775) likewise had striking cytokinetic effects, including features suggestive of premature entry into mitosis during early S-phase. 19,20 Of the Wee1 inhibitors, MK-1775 is currently the most advanced in clinical development, and it is reported to be highly selective toward Wee1 (21). As a single agent it appears to be well tolerated, but has little anti-cancer activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Wee1 potentiates DNA-damaging chemotherapeutics and radiotherapy and has cytotoxic effects as a single agent (19)(20)(21)(22). The consensus view is that Wee1 inhibition facilitates tumor cell killing through G 2 /M checkpoint inactivation, which would catalyze mitotic catastrophe (23)(24)(25).…”
mentioning
confidence: 99%
“…For this reason, it has been speculated that p53-deficient malignant cells are highly dependent on the S and G 2 /M checkpoints for maintaining their genomic integrity. Accordingly, a variety of kinase inhibitors have been developed as cancer therapeutics that inhibit CHK1, CHK2, or WEE1, the known enforcers of these later checkpoints (21,22). We speculated that even though normal T cells have intact p53, their extraordinarily rapid rate of division would also make them exquisitely dependent on the S and G 2 /M checkpoints for survival.…”
Section: Inhibition Of Cell Cycle Checkpoint Kinases Selectively Killmentioning
confidence: 99%